2017
DOI: 10.12891/ceog3235.2017
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of curcumin on ovarian reserve in a rat ischemia model: an experimental study

Abstract: Purpose of investigation:To determine the protective effect of curcumin on ovarian reserve in a rat ischemia model. Materials and Methods: Thirty female Albino rats were randomly divided into two groups by time of unilateral, left ovary ischemia/reperfusion (group 1: two-hour ischemia / two-hour reperfusion; group 2: four-hour ischemia / four-hour reperfusion). Each group was subdivided into three subgroups, sham, control, and curcumin (intraperitoneal curcumin (200 mg/kg) simultaneously with reperfusion). His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Later, the same group investigated the potential effect of curcumin on ovarian reserve in the I/R rat models. Compared with the untreated group, the level of anti‐Mullerian hormone (AMH) in ovarian tissues derived from I/R models exposed to 200 mg/kg of curcumin at the same time as reperfusion was significantly increased (Eser et al, 2017). It has recently been shown that the primary mechanism of curcumin‐mediated restoration of ovarian reserve is through regulation of the Phosphatase and tensin homolog‐Protein kinase B‐Forkhead box class O 3a pathway (Lv et al, 2021).…”
Section: Introduction To Ischemia–reperfusion Injurymentioning
confidence: 99%
“…Later, the same group investigated the potential effect of curcumin on ovarian reserve in the I/R rat models. Compared with the untreated group, the level of anti‐Mullerian hormone (AMH) in ovarian tissues derived from I/R models exposed to 200 mg/kg of curcumin at the same time as reperfusion was significantly increased (Eser et al, 2017). It has recently been shown that the primary mechanism of curcumin‐mediated restoration of ovarian reserve is through regulation of the Phosphatase and tensin homolog‐Protein kinase B‐Forkhead box class O 3a pathway (Lv et al, 2021).…”
Section: Introduction To Ischemia–reperfusion Injurymentioning
confidence: 99%